A Triple Helix Approach to Prioritizing Key Problems in Zakat Performance: An Analytic Network Process Study from South Sulawesi - Azwar, Azwar; Usman, Abur Hamdi; Ravi Abdullah, Mohd Farid (Management of Zakat and Waqf Journal (MAZAWA), 2026)
Zakat holds substantial potential as an Islamic social finance instrument for poverty alleviation and inclusive economic development; however, its performance in many regions remains   constrained not only by governance inefficiencies but also by limitations in how zakat management problems are identified and analyzed. Existing studies often rely on partial, single-actor, or linear approaches that fail to capture the complex interdependencies among stakeholders, resulting in less accurate prioritization of key issues. This limitation necessitates a more integrative and multi-actor analytical framework. Grounded in the Triple Helix framework, this study conceptualizes zakat governance as an interactive system involving experts (academia), regulators (government), and practitioners (zakat institutions). The study aims to identify and prioritize key problems affecting zakat performance in South Sulawesi by integrating these multi-actor perspectives within a structured decision-making model. This study employs the Analytic Network Process (ANP) to capture the interdependencies among problem clusters across institutional, community, and government dimensions. The results indicate that institutional problems constitute the most critical constraint to zakat performance, followed by government and community problems. Key institutional bottlenecks include weak governance, inadequate service quality, and low transparency and accountability. At the community level, low public zakat literacy emerges as the dominant barrier, while the absence of integrated data systems and weak local government support represent major governmental constraints. The findings imply that improving zakat performance requires coordinated and sequenced reforms encompassing regulatory coherence, institutional governance strengthening, and community engagement.